English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

A = B

A^2 = (A)(B)

A^2 - B^2 = AB - B^2

(A - B) (A + B)= B(A - B)

A + B = B

B + B = B

2B = B

2 = 1

I just want to see how many people figure it out because it took me a while to get it

2006-12-31 04:27:53 · 13 answers · asked by Anonymous in Science & Mathematics Mathematics

13 answers

You divided by 0 (A - B).

Although, to be fair, it took me a while to realize that. I sat there staring at the proof and not even questioning the division by A - B.

It can be easy to overlook such small things when it's laid out nicely before you.

And in math, you just accept it when you divide both sides by the same value that it's easy to overlook the fact that you're performing an impossible task.

I love that "proof."

2006-12-31 04:29:34 · answer #1 · answered by Rev Kev 5 · 4 2

Which part of this theorem is wrong?
A = B

A^2 = (A)(B)

A^2 - B^2 = AB - B^2

(A - B) (A + B)= B(A - B)

A + B = B.........Wrong. Since A-B = 0, A+B and B can be any number.

B + B = B

2B = B

2 = 1

2006-12-31 12:32:29 · answer #2 · answered by sahsjing 7 · 1 2

Well A + B cant be = B because u initially said that A= B then
A + B = 2B
B+B is also not equal to B
and 2B is no equal to this impossible. Well unless A and B are both zero !
Anyways 2 can never be equal to 1 this is false!

2006-12-31 12:33:15 · answer #3 · answered by Anonymous · 1 1

You can’t factor out (A-B) because that is dividing, and if A = B, A- B = 0, and division by zero is meaningless.

31 DEC 06, 1858 hrs, GMT.

2006-12-31 13:53:35 · answer #4 · answered by cdf-rom 7 · 1 2

These are all wrong
(A - B) (A + B)= B(A - B)

A + B = B

B + B = B

2B = B

2 = 1

2006-12-31 12:41:15 · answer #5 · answered by Suhas 2 · 0 4

2 cant equal 1

2006-12-31 12:29:13 · answer #6 · answered by lostonthevoid 2 · 0 4

You are making many assumptions and without knowing exactly what "universe" you are working with, these assumptions may or may not be valid. for instance if A=B=0, then cancelation is not possible.

2006-12-31 15:10:18 · answer #7 · answered by hippychick 2 · 0 2

Line 4. You are dividing by zero by cancelling the (A-B) term.

2006-12-31 12:32:21 · answer #8 · answered by Jess 2 · 1 2

You divided by 0 (you divided by (A-B) which is 0 since A=B) when you evaluated:
A + B = B
from:
(A - B) (A + B)= B(A - B)

2006-12-31 12:34:36 · answer #9 · answered by Truth Seeker 2 · 1 2

in the step

(A - B) (A + B)= B(A - B),

both sides are being multiplied by zero.

Took me a few minutes too 8^)

2006-12-31 12:32:51 · answer #10 · answered by Gary H 6 · 1 2

fedest.com, questions and answers